PRODUKTIVITAS HASIL TANGKAPAN BUBU PADA TERUMBU KARANG BUATAN DI PULAU PRAMUKA, KEPULAUAN SERIBU, DKI JAKARTA - Baskoro, Mulyono S.; Yusfiandayani, Roza; Nabiu, Nur Lina Maratana (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Artificial reef made of coconut shell is an artificial habitat which is created to resemble the characteristics of natural reefs and become the alternative to improve the natural coral reefs that have been damaged. The opportunity of artificial reef utilization was researched by using experimental fishing and laboratory observe methods. The use of experimental fishing is to do the catching proses around the artificial reefs. The research was done in August 2013. Laboratory observe was done in September 2013 by observe the sample of fish intestines to get the data of abundance plankton from the inside of fish stomach. The results showed that 64 fishes was catches by bubu consist of 12 species. Red Breast Wrasse (Cheilinus fasciatus) from family Labridae is the dominant species. The plankton composition from the laboratory observe showed that Rhizosolenia and Leptocylindricus are the dominant plankton which indicate that the water is on good condition. Artificial diversity index ranged between 0,52-0,66; the uniformity index ranged between 0,17-0,21 and dominance index-0,45.